The influence of Corporate Governance and company profitability towards the rank of bonds - Delli Maria (Jurnal Ilmiah ESAI, 2014)
The research is to empirically prove whether corporate governance mechanism and profitability influence the rank of bond. The research used some companies registered in JSE and issued bonds during 2008-2011 as the samples taken purposively. The hypotheses were tested through multivariate analysis with ordinal logistic regression. With reliability value 95% , the research indicates that institutional ownership, managerial ownership and independent commissioner board do not influence the rank of the bonds, while the auditing committee, the quality of auditing and ROA are influential to the rank of the bonds.key words: Corporate Governance, profitability , bond rank.